1992
DOI: 10.1159/000154042
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Biology: A Comment on the Significance of the Elston-Stewart Algorithm

Abstract: This article recounts the background to the development of the Elston-Stewart algorithm for the genetic analysis of pedigree data. The algorithm can be used in the context of two contrasting research programmes. The first approach is analytical and reductionist. Traditional biological disciplines, such as physiology, embryology and comparative biology, describe phenomenological domains in which biological organisms are treated as complex systems with emergent properties. In the reductionist approach, these bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A number of researchers have promoted the value of viewing psychiatric problems and mental disorders in the context of complexity science [Merikangas et al, 2006;Stewart, 1992]. The concept of emergence is implicit in much of the thinking about how behavioral styles and patterns of cognition arise from the non-linear interaction of underlying factors ranging from the molecular, anatomical, and symptom levels.…”
Section: Concept Of Emergencementioning
confidence: 99%
“…A number of researchers have promoted the value of viewing psychiatric problems and mental disorders in the context of complexity science [Merikangas et al, 2006;Stewart, 1992]. The concept of emergence is implicit in much of the thinking about how behavioral styles and patterns of cognition arise from the non-linear interaction of underlying factors ranging from the molecular, anatomical, and symptom levels.…”
Section: Concept Of Emergencementioning
confidence: 99%
“…As mentioned in the introduction, the perspective of this paper has been to enrol formal genetics in order to frame questions that it may only be possible to answer by articulating the genetics with experimental physiology [4,7]. More specifically, the major conclusion of this paper is that susceptibility alleles for multifactorial genetic diseases appear to be high, 20% or even more; if correct, this calls for a substantial shift in perspective.…”
Section: Stewartmentioning
confidence: 99%
“…However, this does not exactly correspond to the original motivation of one of its authors. As explained by Stewart [4], the initial impetus for developing the E-S algorithm came from the work of Thoday [5], who showed that the 'polygenes' responsible for quantitative variation in Drosophila were limited in number and could be individually identified. Building on this, Spickett [6] showed that the 'polygenes' thus identified each had distinct, characteristic developmental and physiological effects.…”
Section: Introductionmentioning
confidence: 99%